Diversity of fruit flies (Diptera: Tephritidae) from the South African highveld and lowveld : a preliminary assessment of Wolbachia infection - Weldon, Christopher W. (University of Pretoria, 2023)
Dissertation (MSc (Entomology))--University of Pretoria, 2022.